Pyrene-Imidazole Based Aggregation Modifier Leads to Enhancement in Efficiency and Environmental Stability for Ternary Organic Solar Cells - Lin, Hui; Du, Xiaoyang; Li, Lijuan; Zheng, Caijun; Tao, Silu (Frontiers in Chemistry, 2018)
A novel pyrene-imidazole derivative (PyPI), which can form effcient π-π stacking in solid film, has been utilized in organic solar cells (OSCs). The stacking of small a molecule PyPI can facilitate a charge transfer and suppress fullerene aggregation. As a result, PTB7-Th: PyPI: PC71BM based ternary OSC exhibits a high power conversion efficiency (PCE) of 10.36%, which presents a 15.88% increase from the binary device (8.94%). Concurrently, the ternary OSC shows a much better thermal and light illumination stability. Under continuous 60°C annealing for 3 h, in atmosphere, the device still remains at 94.13% efficiency more than the pristine state, while the control device remains at 52.47% PCE. Constant illumination under Air Mass (AM) 1.5G irradiation (100 mW cm−2) in atmosphere, the PCE of OSC remains at 72.50%. The high conversion efficiency and excellent environmental stability of the PyPI based ternary OSC, has narrowed the gap between laboratory investigation and industrial production.